Дія в часі кримінально-правових норм, які передбачають відповідальність за зловживання впливом - Лащук, Н.; Lashchuk, N. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Досліджено співвідношення раніше чинних норм, що передбачали відповідальність за зловживання впливом та відповідної законодавчої новели, а також їх темпоральну дію. Констатовано необхідність перегляду вироків щодо осіб, які раніше вчинили діяння, що нині охоплюються ст. 369-2 КК України, але були засуджені за одержання хабара. Автор доводить, що у внесенні змін щодо норм, які регулюють кримінальну відповідальність за «лобізм», немає жодної системи; у результаті безсистемності внесення змін у досліджувані норми кримінальна відповідальність то посилювалася, то пом’якшувалася; збільшився обсяг криміналізації щодо зловживання впливом (коло діянь, за які передбачається кримінальна відповідальність, перелік осіб, які можуть бути суб’єктами цього злочину). In the article the correlation between earlier existing rules providing responsibility for abuse of influence and the corresponding legislative novel from the aspect of the general and special norms has been investigated. Action of laws on criminal responsibility for abuse of influence in time has been considered. Therefore, it has been established that no system exists in modification concerning the norms regulating criminal liability for «lobbyism»: as a result of modification criminal responsibility either intensified or softened; the degree of criminalization of abuse of influence (a circle of actions for which criminal responsibility is provided, the list of persons who can be subjects of this crime) increased; sanctions of Article 368-2 of the Criminal Code of Ukraine are softer than those of Article 368 of the Criminal Code of Ukraine which provided criminal responsibility for the considered actions before they became a separate norm. Consequently there is some grounding for revision of sentences concerning people, who earlier made acts, now they are under Article 369-2 of the Criminal Code of Ukraine, but were condemned for bribery.
Action of the Criminal Legal Norms Providing Responsibility for Abuse of Influence in Time
Keywords: зловживання впливом; неправомірна вигода; хабар; дія закону про кримінальну відповідальність в часі; abuse of influence; illegal benefit; a bribe; action of the criminal law in time